Sai Coating : detonation spray gun - Sahay, Arvind (London : Indian Institute of Management, Ahmedabad, 2019)
Sai Coating, a small entrepreneurial firm, was one of the three firms that had received the license from ARCI for marketing the Detonation Spray coating (DSC). Sai Coating made and sold D-Gun to the wire drawing segment and was looking at three other sectors, namely: Textiles, Turbine and Aero Components. The coating enhanced the life of the coated wire or surface and its functionality in some ways. The firm had a turnover of INR 4,500,000 and was looking to generate scale and maximize its revenues.
Originally Published InSahay, A. (2019). Sai Coating: Detonation Spray Gun. IIMA/MAR0505. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Protective coatings industry -- India -- Case studies; Metal spraying -- Case studies